Internal potassium stimulates the sodium-potassium pump by increasing cell ATP concentration. - Sachs, J R (1981)
1. Intracellular K increases the ouabain-sensitive Na-K exchange in human red blood cells. Pump rate increases hyperbolically with internal K with a K12 for K of 2.58 m-mole/l. red blood cells. Li also stimulates the pump rate, but with a much higher K12. The stimulation does not result from a change in the affinity of the pump for its substrates Na, K or Mg or for the product, phosphate. 2. The effect of cell K on the Na-Na exchange is biphasic. At low concentrations it decreases the exchange rate but then the exchange increases linearly with cell k concentration. 3. Stimulation of the pump rate by internal K can be demonstrated in reconstituted ghosts but only if the ratio of the volume of cells to that of solution at the time of haemolysis is high. Stimulation is not observed if the ghosts contain an efficient system for rephosphorylating ADP to ATP, such as creatine phosphate and creatine kinase, or if the measurements are made with iodoacetamide which inhibits rephosphorylation of ADP by inhibiting the enzyme glyceraldehyde-3-phosphate dehydrogenase. 4. Cells with low internal K and Li have low ATP concentrations, and ATP increases hyperbolically with internal K or Li with the same K12 as does the pump rate. In cells depleted of substrate intracellular K does not stimulate the pump rate. 5. The effect of K and Li on the pump rate probably does not result from enhanced activity of any of the enzymes below phosphofructokinase in the glycolytic pathway.